Pengaruh Pola Asuh Orang Tua Bekerja dan Tidak Bekerja dengan Tingkat Kemandirian Anak Usia 7-9 Tahun di Desa Sruni Kabupaten Sidoarjo - Dona Almeyda Susanti; Wiwin Yulianingsih (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2023)
Researchers try to examine whether there is a real influence on the level of independence of children aged 7-9 years in Sruni Village, Sidoarjo Regency based on parenting patterns of working and non-working parents. Researchers hypothesize that parenting and non-working parents have a positive impact on the level of independence of children aged 7-9 years in Sruni Village, Sidoarjo Regency. A causal comparative quantitative approach was used to collect data through questionnaires distributed to relevant respondents via Google Form. The study population consisted of working and non-working parents with children aged 7-9 years in Sruni Village, Sidoarjo District. In this study, the data were sorted with Mircrosoft Excel, and processed with SPSS 22 with T test.The results showed that parenting of non-working parents did not have a positive effect on children's independence, but the results showed that parenting of working parents had a significant and positive effect on shaping children's independence. It is recommended that working parents continue to prioritize quality time to foster the growth and development of their children, while non-working parents must be open-minded towards parenting and education to encourage independence in their children.